Studies on Mathematical Modelling of Influenza in Canada - Delorme, Jordan Michael (My University, 2010)
Two studies are presented that involve the mathematical modelling of the 2009/2010 pandemic H1N1 outbreak in Montreal, Quebec, Canada. The first study uses surveillance data and reported vaccination rates to create a model that can recreate the pandemic. The vaccination is then removed from the model and a simulation is run to determine what the pandemic may have looked like without the vaccination campaign. The number of cases, hospitalizations and deaths averted through the vaccination campaign are estimated. The second study recreates both waves of the pH1N1 pandemic by allowing absolute humidity and contacts to change over time. The effect of school reopening in the fall and the effect of schools not opening in the fall are analyzed. Also, estimates for the reporting efficiency are made for each age group studied. Incorporating absolute humidity changes and the summer school closure allows the model to accurately recreate both incidence waves
Keywords: Biology; Biology